2018
DOI: 10.3390/metabo8010019
|View full text |Cite
|
Sign up to set email alerts
|

Carbonic Anhydrases: Role in pH Control and Cancer

Abstract: The pH of the tumor microenvironment drives the metastatic phenotype and chemotherapeutic resistance of tumors. Understanding the mechanisms underlying this pH-dependent phenomenon will lead to improved drug delivery and allow the identification of new therapeutic targets. This includes an understanding of the role pH plays in primary tumor cells, and the regulatory factors that permit cancer cells to thrive. Over the last decade, carbonic anhydrases (CAs) have been shown to be important mediators of tumor cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
195
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 212 publications
(199 citation statements)
references
References 225 publications
4
195
0
Order By: Relevance
“…Indeed, it has been shown that pH i in the cytoplasm of tumor cells (pH 7. 2-7.4) is similar to that of normal cells (10,11) . However, the pH e surrounding tumor cells is strongly acidic (pH 6.5-6.8) (11).…”
Section: Introductionsupporting
confidence: 73%
See 3 more Smart Citations
“…Indeed, it has been shown that pH i in the cytoplasm of tumor cells (pH 7. 2-7.4) is similar to that of normal cells (10,11) . However, the pH e surrounding tumor cells is strongly acidic (pH 6.5-6.8) (11).…”
Section: Introductionsupporting
confidence: 73%
“…There is additional evidence that CA IX forms functional interactions with specific ion transporters accelerating their activity (24,29,30). It has been hypothesized that CA IX forms a metabolon with these transporters and CA II to maintain the glycolytic phenotype by 'cycling' substrates between tumors cells and the microenvironment to regulated pH i (10,16,23,24,(29)(30)(31). Our lab, and others, have also hypothesized that CA IX serves to regulate pH e by responding to changes in substrate concentration (10,19,20).…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…A wealth of functional studies has been accumulated over the years on hCA IX, showing that this enzyme is actively involved in survival, proliferation, invasion, and metastasis of cancer cells by means of several mechanisms, which involve all its different domains. 7,9,52,80,81 Among these mechanisms, the tumor pH regulation carried out by the CA domain 80,82 plays a key role in survival, migration, and invasion of cancer cells. 24,[83][84][85][86] The involvement of hCA IX in regulating pH of hypoxic tumor cells can be schematically summarized as follows ( Figure 5).…”
Section: Migration and Invasion Of Tumor Cellsmentioning
confidence: 99%